Comparative Analysis of Whole-Transcriptome RNA Expression in MDCK Cells Infected With the H3N2 and H5N1 Canine Influenza Viruses - Tao, Pan; Ning, Zhangyong; Hao, Xiangqi; Lin, Xi; Zheng, Qingxu; Li, Shoujun (Frontiers in Cellular and Infection Microbiology, 2019)
This study aimed to detect the changes in the total transcriptome of MDCK cells after infection by the H5N1 and H3N2 canine influenza viruses with high-throughput sequencing, search for the differential expression of transcriptome MDCK cells after infection with H5N1 and H3N2 through comparative analysis, and then explain the different pathogenicity of H5N1 and H3N2 at the transcriptome level. Through comparative analysis, we found that the H3N2 infection group had 2464 mRNAs, 16 miRNAs, 181 lncRNAs, and 262 circRNAs with significantly different expression levels. The H5N1 infection group had 448 mRNAs, 12 miRNAs, 77 lncRNAs, and 189 circRNAs showing significant differences in expression. The potential function was predicted by GO and KEGG analyses of the target genes of miRNA, lncRNA and circRNA, and the ncRNA-mRNA regulatory network was constructed based on differentially expressed RNA. The results showed that the H3N2 infection group had more regulatory pathways of immune metabolism than the H5N1 infection group, which may be one reason why the H3N2 influenza virus is less pathogenic than the H5N1 influenza virus. This study provided detailed data on the production of ncRNA during the infection of MDCK cells by the canine influenza viruses H3N2 and H5N1, analyzed the differences in the total transcriptome between H3N2- and H5N1-infected MDCK cells, and then explained the differences in the pathogenicity of H3N2 and H5N1 at the transcriptional RNA level.